Microplastic induces soil water repellency and limits capillary flow - Andreas Cramer; Pascal Benard; Mohsen Zarebanadkouki; Anders Kaestner; Andrea Carminati (Vadose Zone Journal, 2023)
Abstract Soils are considered the largest sink of microplastic (MP) in terrestrial ecosystems. However, little is known about the implications of MP on soil physical properties. We hypothesize that low wettability of MP induces soil water repellency, depending on MP content and size of MP and soil particles. We quantified wettability of mixtures of MP and sand. The sessile drop method (SDM) was applied to measure static contact angle (CA) of MP and glass beads at contents ranging from 0 to 100% (w/w). The results are extrapolated to varying combinations of MP and soil particle sizes based on specific surface area. Capillary rise was imaged with neutron radiography quantifying the effect of MP on dynamic CA, water imbibition, and water saturation distribution in sand. At 5% (w/w) MP content, static CA exhibited a steep increase to 80.2° for MP 20–75 μm and 59.7° for MP 75–125 μm. Dynamic CAs were approximately 40% lower than static CAs. Capillary rise experiments showed that MP 20–75 μm reduced water imbibition into sand columns (700–1,200 μm), with average dynamic CA of 40.3° at 0.35% (w/w) MP content and 51.8° at 1.05%. Decreased water saturation and increased tortuosity of flow paths were observed during imbibition peaking at 3.5% (w/w) local MP content. We conclude, in regions with high MP content. water infiltration and thus MP transport are hindered. Local low wettability induced by MP is expected to limit soil wettability and impede capillary rise.